Burden of non-CO poisoning in 204 countries and territories, 1990–2021: results from the global burden of disease study 2021 - Lei, Rong; Yue, Chaofu; Yue, Feng; Gao, Hong; He, Xing; Yan, Qinyong; Yang, Zhigang; Bao, Wei; Hu, Caimei; Ma, Qingsong; Yang, Mei (Frontiers in Public Health, 2025)
BackgroundNon-carbon monoxide (non-CO) poisoning remains a significant global public health issue, contributing to considerable morbidity and mortality. However, there is a lack of comprehensive analysis regarding the global burden and trends of non-CO poisoning.MethodsData from the Global Burden of Disease (GBD) 2021 study were used to assess the global, regional, and national prevalence, mortality, and disability-adjusted life years (DALYs) associated with non-CO poisoning from 1990 to 2021. Descriptive statistical methods were applied to assess global, regional, and national trends in non-CO poisoning burden, with estimates of prevalence, mortality, and DALYs. Smoothing splines models were used to examine the relationship between non-CO poisoning burden and the Socio-Demographic Index (SDI).ResultsIn 2021, global non-CO poisoning accounted for 3.58 million prevalent cases (ASPR: 43.34/100,000), 27.26 thousand deaths (ASDR: 0.35/100,000), and 1.65 million DALYs (ASR: 21.72/100,000), with respective declines of 43.9, 38.9, and 43.5% since 1990. The burden of non-CO poisoning varies significantly across countries and regions, overall, the burden of non-CO poisoning shows a negative correlation with the SDI, with regions and countries with lower SDI values experiencing higher rates of poisoning-related harm. Children under 5 years old and the older adult bear a higher disease burden, with males generally experiencing higher disease burden than females.ConclusionAlthough the global burden of non-CO poisoning has decreased, low- and middle-income countries (LMICs), especially those with lower SDI, continue to experience a disproportionately high burden. Future research should focus on agent-specific epidemiology, improving data collection in LMICs, and examining the impact of agricultural and environmental exposures. Targeted interventions for vulnerable populations, such as children and the older adult, as well as the integration of mental health considerations into prevention strategies, are essential for reducing the global burden.